2005
DOI: 10.2114/jpa.24.541
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-term Exercise in the Heat on Thermoregulation, Blood Parameters, Sweat Secretion and Sweat Composition of Tropic-dwelling Subjects

Abstract: This study investigates the effects of a shortterm aerobic training program in a hot environment on thermoregulation, blood parameters, sweat secretion and composition in tropic-dwellers who have been exposed to passive heat. Sixteen healthy Malaysian-Malay male volunteers underwent heat acclimation (HA) by exercising on a bicycle ergometer at 60% ofVO 2 max for 60 min each day in a hot environment (Ta: 31.1Ϯ0.1°C, rh: 70.0Ϯ4.4%) for 14 days. All parameters mentioned above were recorded on Day 1 and at the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 45 publications
6
63
1
3
Order By: Relevance
“…In fact, they had a normal diet sodium content (ϳ2000 mg/day) and this may be the reason for the nonsignificant change in sweat sodium concentration in the present study. Studying HA on Malaysian subjects, Saat et al (2005b) observed higher sweat sodium concentration at rest after the protocol and a nonsignificant difference in sweat sodium concentration during exercise. It is known that sweat sodium concentration is influenced by sweat rate because electrolyte reabsorption is diminished due to augmented sweat rate (Saat et al, 2005b).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In fact, they had a normal diet sodium content (ϳ2000 mg/day) and this may be the reason for the nonsignificant change in sweat sodium concentration in the present study. Studying HA on Malaysian subjects, Saat et al (2005b) observed higher sweat sodium concentration at rest after the protocol and a nonsignificant difference in sweat sodium concentration during exercise. It is known that sweat sodium concentration is influenced by sweat rate because electrolyte reabsorption is diminished due to augmented sweat rate (Saat et al, 2005b).…”
Section: Discussionmentioning
confidence: 89%
“…Studying HA on Malaysian subjects, Saat et al (2005b) observed higher sweat sodium concentration at rest after the protocol and a nonsignificant difference in sweat sodium concentration during exercise. It is known that sweat sodium concentration is influenced by sweat rate because electrolyte reabsorption is diminished due to augmented sweat rate (Saat et al, 2005b). To take this effect into account, we divided local sweat sodium concentration by local sweat rate.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Participants cycled at a fixed mechanical intensity to elicit 50% 2peak for 45 minutes (Nielsen et al, 1997;Saat, et al, 2005) once a day for 4 consecutive days within 35.2±0.5°C and 60±2% RH (SDHA), within 21.7±0.6°C and 39±5% (CON), or twice daily for two consecutive days within 35.4±0.8°C and 61±3% RH (TDHA). Cycling exercise was chosen as it is non-weight-bearing and practical, thus reducing injury risk and enabling 4 to 6 participants to train simultaneously.…”
Section: Heat Acclimation and Temperate Trainingmentioning
confidence: 99%
“…The threshold for impaired exercise thermoregulation is 1% dehydration, and at 4%, decrements of 20 -30% are seen in work capacity (8). Hypohydration decreases cutaneous vasodilation and sweating during heat stress (30,31). Hypovolemia and hyperosmolality due to thermal dehydration also suppress thermoregulatory responses of sweating and cutaneous vasodilation, resulting in increased risk of heat illness (18).…”
Section: Research Articlementioning
confidence: 99%